Dystrybucja usług ubezpieczeniowych w Polsce w latach 1998-2005 - Kufel-Siemińska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the recent years, the distribution of insurance services has become a crucial tool for the competition among insurance companies. The ways of the distribution of insurance services are subject to huge changes as the factors taken into account by its selection, such as expectations of the purchasers, are changing. In the Polish market, the crucial role is played by the agency channels (above all in the sales of life insurances). The share of the direct channels of distribution is declining, whereas the biggest insurance companies in Poland in terms of every branch (PZU SA PZU Życie SA) are mostly using the direct channels of distribution. The insurance brokers are particularly active in the distribution of non life insurance services. As more often the insurances are successfully distributed through the products' distribution channels, with regard to which they are complementary, more often their users at the same time belong to other businesses than insurance. The participation of banks in the distribution of insurance services is particularly increasing, what is one of the signs of the development of bancassurance in our market. The increasing number of subjects is using unconventional methods of distribution of insurance services. There is also an increase in the importance of the subjects supporting the functioning of the distribution channels of insurance services. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 207-214